Perbandingan hasil belajar fisika siswa SMA Negeri 15 Padang menggunakan e-modul dan video berbasis CTL materi hukum newton tentang gerak dan gravitasi - Silmi Hidayatullah03; Desnita Desnita; Yenni Darvina; Asrizal Asrizal (Universitas Negeri Padang, 2020)
The learning process demanded by the 2013 curriculum is contextual learning and students are more active in finding non-teacher knowledge which is a source of knowledge. In reality, student learning outcomes are still low and do not involve contextual learning. The solution to this problem is to apply learning resources that emphasize students can learn independently and associate the environment in the learning process. This study aims to determine differences in student learning outcomes using CTL-based E-modules and CTL-based learning videos at SMAN 15 Padang. This type of research is quasi-experimental research with a Randomized Posttest Only Control Group Design research design. The population in this study were all students of class X SMAN 15 Padang registered in the 2019/2020 Academic Year. Sampling in this study was conducted by combining purposive sampling and cluster random sampling techniques. The sample in this study was class X MIA 4 as Experiment 1 class and class X MIA 5 as Experiment 2 class as many as 72 students. In the analysis of self and social attitude competency data and knowledge of normal and homogeneous distributed data, then through the two average similarity test, on the competence of self and social attitudes obtained tcount = 3.32 and on the knowledge competency tcount = 3.87, while the value T table (0.975; 70) = 1.9966 which proves that the value of Thitung is greater than T table, with acceptance criteria Ho if or -1.996 <th <1.996, it can be concluded that Ho is rejected and Hi is accepted, meaning that there are significant learning outcomes between application of CTL-based E-modules with CTL-based Learning Videos.